2017
DOI: 10.1038/s41598-017-17221-4
|View full text |Cite
|
Sign up to set email alerts
|

Design of plasmonic Ag-TiO2/H3PW12O40 composite film with enhanced sunlight photocatalytic activity towards o-chlorophenol degradation

Abstract: A series of plasmonic Ag-TiO2/H3PW12O40 composite films were fabricated and immobilized by validated preparation technique. The chemical composition and phase, optical, SPR effect and pore-structure properties together with the morphology of as-prepared composite film are well-characterized. The multi-synergies of as-prepared composite films were gained by combined action of electron-capture action via H3PW12O40, visible-response induced by Ag, and Schottky-junction formed between TiO2-Ag. Under simulated sunl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Examinations of possible photocatalytic mechanism of ZCS heterostructures were carried out based on the trapping tests of active scavengers [27, 28]. Na 2 -EDTA, AgNO 3, and IPA were engaged to trap the photogenerated holes (h + ), electrons (e − ) and hydroxyl radicals (·OH) in the solutions, respectively, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Examinations of possible photocatalytic mechanism of ZCS heterostructures were carried out based on the trapping tests of active scavengers [27, 28]. Na 2 -EDTA, AgNO 3, and IPA were engaged to trap the photogenerated holes (h + ), electrons (e − ) and hydroxyl radicals (·OH) in the solutions, respectively, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As-prepared TiO2/H3PW12O40/Ag film showed the excellent photocatalytic property, the results showed that Kapp of as-prepared TiO2/H3PW12O40/Ag reaction system increased significantly in comparison with TiO2 system (P < 0.05). Because TiO2/H3PW12O40/Ag reaction system delayed the recombination of holes and electrons pairs efficiently owing to the synergistic effects between the Keggin unit and TiO2 and the generation of Schottky junction at the interface between Ag and TiO2, meanwhile expanded the absorption of visible-light due to SPR effect (Lu et al, 2017). It is worth noting that only a limited amount of ca.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that •OH is a very strong activator as well as ortho-and para-directing in electrophilic aromatic substitution (Antonaraki et al, 2002). Therefore, •OH radical that was confirmed as the main role in TiO2/H3PW12O40/Ag reaction system (Lu et al, 2017) can directly attack the electron-rich positions in CPs molecules with a rapid degradation rate.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations